Strongly enlarged topological regime and enhanced superconducting gap in nanowires coupled to Ising superconductors - Yingming Xie; Benjamin T. Zhou; T. K. Ng; K. T. Law (Physical Review Research, 2020)
An external magnetic field is needed to drive a nanowire in proximity to an s-wave superconductor into a topological regime which supports Majorana end states. However, magnetic field generally suppresses the proximity superconducting gap induced on the nanowire. In recent experiments using InSb nanowires coupled to conventional superconductors such as Al and NbTiN, the induced proximity gap vanishes at magnetic fields B∼1 T. This results in a small superconducting gap on the wire and a narrow topological regime which is proportional to the strength of the magnetic field. In this work, we show that by placing nanowires in proximity to recently discovered Ising superconductors such as the atomically thin transition-metal dichalcogenide NbSe_{2}, the topological superconducting gap on the wire can be maintained at a large magnetic field as strong as B∼10 T. This robust topological superconducting gap is induced by the unique equal-spin triplet Cooper pairs of the parent Ising superconductor. The strong magnetic field allows a topological regime ten times larger than those in InSb wires coupled to conventional superconductors. Our work establishes a realistic platform for building robust Majorana-based qubits.